THE EUROPEAN FUND FOR STRATEGIC INVESTMENTS – PRIORITY OF THE EUROPEAN COMMISSION DURING JUNCKER MANDATE - Domnica-Doina PÂRCĂLABU (Hyperion Economic Journal, 2014)
On July 15, 2014 Jean-Claude Juncker was elected President of the European Commission (EC) by the European Parliament (EP) following the presentation of the Political Guidelines for the next European Commission – A New Start for Europe: My Agenda for Jobs, Growth, Fairness and Democratic Change. With a vision of a European Union that is bigger and more ambitious on big things, and smaller and more modest on small things, Juncker has proposed a renewed European Union (EU) highlighting ten policy areas. The priority policy areas are aimed at employment, growth and investment, the digital single market, and the energy union.